2013
DOI: 10.1515/bnm-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

Blood protein and blood cell interactions with gold nanoparticles: the need for in vivo studies

Abstract: Gold nanoparticles (GNPs) have gained in prominence within the field of nanomedicine with recent advancement of several embodiments to clinical trials. To ensure their success in the clinic it has become increasingly clear that a deeper understanding of the biological interactions of GNPs is imperative. Since the majority of GNPs are intended for systemic intravenous use, an immediate and critical biological interaction is between the blood and the GNP. Blood is composed of plasma proteins and cells. Both of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…However, NPs that escapes from the natural mechanism of excretion, gets retained in cells and tissues resulting in NP-induced toxicity . Furthermore, NPs that are administered through intravenous delivery enter the vascular system, thereby interacting with the blood proteins and blood cells . Proteins in the blood adsorb on the surface of NPs (opsonization) facilitating the process of phagocytosis through monocytes and macrophages resulting in its elimination from the circulatory system. , However, erythrocytes, which make up 96% of the blood cells are devoid of phagocytic machinery.…”
Section: Resultsmentioning
confidence: 99%
“…However, NPs that escapes from the natural mechanism of excretion, gets retained in cells and tissues resulting in NP-induced toxicity . Furthermore, NPs that are administered through intravenous delivery enter the vascular system, thereby interacting with the blood proteins and blood cells . Proteins in the blood adsorb on the surface of NPs (opsonization) facilitating the process of phagocytosis through monocytes and macrophages resulting in its elimination from the circulatory system. , However, erythrocytes, which make up 96% of the blood cells are devoid of phagocytic machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Another cellular constituent of blood, which is often overlooked in terms of contribution to hemostasis, is represented by leukocytes. These cells are subdivided into monocytes, granulocytes and lymphocytes (Table 2) and play a critical role in inflammation, immunity and host defense systems [66]. However, recent studies have also found that these cells actively contribute to normal hemostasis as well as thrombotic conditions [67].…”
Section: Leukocyte Function In Hemostasis and The Mechanisms Involmentioning
confidence: 99%
“…Another important observation is that a positive charge on the surface of NPs can, in addition to warranting effective cellular drug delivery, also ensue immunotoxicity through the stimulation of inflammatory immune responses. Several researchers have found that cationic liposomes can stimulate neutrophils and induce oxidative bursts in these cells [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,...…”
Section: Leukocyte Function In Hemostasis and The Mechanisms Involmentioning
confidence: 99%
“…Within minutes of the intravenous injection of AuNPs, erythrocytes, monocytes, macrophages, neutrophils, and dendritic cells recognize the AuNPcorona complexes, phagocytosing nearly 95% of the injected dose. This leads to the eventual destruction and removal of the AuNPs from the blood stream without ever reaching the tumor [226]. Considering these barriers, maximizing the delivery of AuNPs in solid tumors must undoubtedly involve the study of interactions with blood.…”
Section: Introductionmentioning
confidence: 99%